2017
DOI: 10.1007/s11274-017-2261-2
|View full text |Cite
|
Sign up to set email alerts
|

Is Drosophila-microbe association species-specific or region specific? A study undertaken involving six Indian Drosophila species

Abstract: The present work aims to identify the microbial diversity associated with six Indian Drosophila species using next generation sequencing (NGS) technology and to discover the nature of their distribution across species and eco-geographic regions. Whole fly gDNA of six Drosophila species were used to generate sequences in an Illumina platform using NGS technology. De novo based assembled raw reads were blasted against the NR database of NCBI using BLASTn for identification of their bacterial loads. We have tried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…As previously reported for a wide range of terrestrial and aquatic invertebrates (Colman et al, 2012;Jones et al, 2013;Mikaelyan et al, 2015;Muturi et al, 2017;Receveur et al, 2020;Singhal et al, 2017;Yun et al, 2014), we found significant differences in the relative abundance, alpha diversity, and beta diversity of the microbiota among host aquatic invertebrate taxa at the levels of genus, family, and order. Core microbiota, which are collections of specific bacterial species commonly shared among all individuals of a host TA B L E 4 P values from Adonis statistical tests measuring beta diversity using the unweighted and weighted UniFrac metrics and the Bray-Curtis dissimilarity metric.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…As previously reported for a wide range of terrestrial and aquatic invertebrates (Colman et al, 2012;Jones et al, 2013;Mikaelyan et al, 2015;Muturi et al, 2017;Receveur et al, 2020;Singhal et al, 2017;Yun et al, 2014), we found significant differences in the relative abundance, alpha diversity, and beta diversity of the microbiota among host aquatic invertebrate taxa at the levels of genus, family, and order. Core microbiota, which are collections of specific bacterial species commonly shared among all individuals of a host TA B L E 4 P values from Adonis statistical tests measuring beta diversity using the unweighted and weighted UniFrac metrics and the Bray-Curtis dissimilarity metric.…”
Section: Discussionsupporting
confidence: 87%
“…A summary of the most common bacterial phyla identified within the microbiota of terrestrial invertebrates (Colman et al, 2012;Hernández-García et al, 2017;Jones et al, 2013;Mikaelyan et al, 2015;Muturi et al, 2017;Pérez-Cobas et al, 2015;Rizzi et al, 2013;Singhal et al, 2017;Yun et al, 2014) and freshwater invertebrates (Ayayee et al, 2018;Pechal & Benbow, 2016;Receveur et al, 2020), fishes (Desai et al, 2012;X. Li et al, 2013;Roeselers et al, 2011;Sullam et al, 2012;Wu et al, 2012), plants (Srivastava et al, 2017;Tanaka et al, 2012), sediments (Zhang et al, 2019), bacterioplankton (Ayayee et al, 2018;Portillo et al, 2012), and biofilms (Ayayee et al, 2018) is shown in Table 7.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To illustrate this, we estimated CUSCO values for several publicly available assemblies of different D. melanogaster strains (supplementary fig. 10; (McCoy et al, 2014;Vicoso and Bachtrog, 2015;Anreiter et al, 2017;Singhal et al, 2017;Chakraborty et al, 2019;Ellison and Cao, 2020)). Assemblies based on ONT and PacBio long reads have a similar quality than our assemblies of Pi2 and Canton-S (supplementary fig.…”
Section: Novel Quality Metricsmentioning
confidence: 99%